2003
DOI: 10.1016/s0042-6989(02)00594-1
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of second-order neurons in the retina of rd/rd mutant mice

Abstract: This is a brief review of data obtained by analyzing the morphology and the physiology of the retinas in rd/rd and normal, wt mice, aged 10-90 days. Second-order neurons of the rd/rd show abnormalities that start with the anomalous development of rod bipolar cells around P10 and culminate with the atrophy of dendrites in cone bipolar cells, mostly evident at P90. Horizontal cells remodel considerably. Cone-mediated ERGs, (recorded between 13 and 16 days of age) have reduced a-wave and b-wave amplitudes and lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
162
2
19

Year Published

2003
2003
2009
2009

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 201 publications
(205 citation statements)
references
References 42 publications
22
162
2
19
Order By: Relevance
“…In addition, in both cell types, irregular processes extending to the ONL were observed. Similar morphological alterations have been found in other mouse models lacking functional cones and/or rods (Strettoi et al, 2003;Claes et al, 2004). Together, these findings strongly suggest that rod photoreceptor inputs are required for the functional maintenance of synaptic contacts.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, in both cell types, irregular processes extending to the ONL were observed. Similar morphological alterations have been found in other mouse models lacking functional cones and/or rods (Strettoi et al, 2003;Claes et al, 2004). Together, these findings strongly suggest that rod photoreceptor inputs are required for the functional maintenance of synaptic contacts.…”
Section: Discussionsupporting
confidence: 84%
“…In addition to direct effects on photoreceptors, the rd͞rd mutation also results in alterations in inner retinal circuitry (32)(33)(34). Similar changes have also been reported in retinas of mice with mutations in the Leber's congenital amaurosis-causing gene Crx (35) and after simple visual deprivation (36,37).…”
Section: Pharmacologic Inhibition Of Visual Retinoid Cycle Causes Lossupporting
confidence: 61%
“…Linberg et al from the OPL has also been reported in the rd degeneratioñ Strettoi & Pignatelli, 2000;Strettoi et al, 2003;Gouras & Tanabe, 2003! which provides another point of contrast to the responses after retinal detachment where rod bipolar cells and horizontal cells rapidly sprout neurites that grow into the ONL and even into the subretinal space~Lewis et al, 1998!.…”
Section: Discussionmentioning
confidence: 85%